Advancing natural language processing in uzbek: challenges and solutions: Advancing natural language processing in uzbek: challenges and solutions - Sattarova , Sapura (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Abstract– Natural Language Processing (NLP) technologies have revolutionized various domains by enabling machines to understand, interpret, and generate human language data. However, for languages with limited digital resources and complex linguistic structures such as Uzbek, NLP faces unique challenges. This paper delves into the specific challenges encountered in NLP for Uzbek, focusing on lemmatization, stemming, sound recognition, and semantic analysis. The paper highlights the importance of addressing these challenges for enhancing NLP capabilities in Uzbek and proposes strategies and solutions to overcome them. By leveraging interdisciplinary collaborations, linguistic expertise, and advanced computational techniques, this paper aims to contribute to the advancement of NLP technologies tailored for Uzbek, ultimately fostering linguistic research, technological innovation, and digital inclusion in Uzbek-speaking communities.